COMPREHENSIVE ASSESSMENT OF VARIOUS FORMS OF CHRONIC CHRONIC NEPHRITIC SYNDROME IN CHILDREN (World Bulletin of Public Health, 2022)
Diseases of the urinary system, according to WHO, currently occupy the 2nd place among the main forms of pathology characteristic of childhood. In the structure of kidney diseases in children hospitalized in the nephrology department, nephritic syndrome ranks second. The disease, which began in children, often continues into adulthood, which leads to a decrease in the quality of life, can cause disability, and sometimes dramatic outcomes. The urgency of the problem of chronic glomerulonephritis is explained not by the prevalence of the disease, but by the course of the disease and the development of renal failure. Chronic nephritic syndrome is one of the severe kidney diseases in children, which is characterized by the frequent development of complications and the progression of the course of the disease. The course of chronic nephritic syndrome depends on various forms of the disease and the clinical characteristics determine the prognosis of the disease